GROWTH OF RED DRAGON FRUIT (Hylocereus polyrhizus (WEBER) BRITTON & ROSE) PLANT SETTINGS AS A RESULT OF DIFFERENT SETTING LENGTH AND ROOTONE-F ZPT CONCENTRATION - Priyatna, Arif; Sondari, Nunung; Amalia, Lia (Papanda Publisher, 2024)
ABSTRACT The increasing demand for red dragon fruit requires the provision of quality seeds. The aim of the study was to examine whether there was an interaction between the length of the cuttings and the concentration of ZPT Rootone-F which affected the growth of the cuttings and to determine the concentration of ZPT Rootone-F at each length of cuttings which produced the best dry weight of cuttings. Experiments using factorial RAK consisted of two factors repeated 2 times. Factor 1: cutting length (p) consisted of 4 levels: 5cm (p1)15cm (p2) 25 cm (p3)35 cm (p4) and the second factor was the concentration of Rootone-F (k): 500 gL-1 water (k1) 700 gL-1 water (k2) 900 gL-1 water (k3) 1100 gL-1 water (k4) Each treatment combination consisted of 6 samples with a total population of 192 cuttings. Cutting lengths of 15cm 25cm and 35cm produced the highest percentage of living cuttings: 91.63 % 97.88 % 97.88% compared to 5cm length: 45.75 %. Fastest shoot emergence time. Length of cuttings 35 cm: 27.19 dap. The highest number of shoots was produced by cuttings lengths of 35 cm and 25 cm, namely 2.2 and 2 shoots. Cutting length of 35 cm produced the longest shoot: 18.77 cm, the highest root volume: 30 cm3, the heaviest shoot fresh weight: 190.75 g and the heaviest shoot dry weight: 148.66 g. Rootone-F concentrations at various levels did not affect all observations. No interactions occurred. between the length of the cuttings and the concentration of rootone-F PGR on the growth of the cuttings, the length of the cuttings independently affected: Percentage of living cuttings (%), time of emergence of shoots (by date), number of shoots (strands), length of cuttings (cm), root volume (cm3) ), shoot fresh weight (g) and shoot dry weight (g). The dry weight of shoots will increase by 4.77 units for each increase in cutting length. Cutting length of 35 cm resulted in the best growth of cuttings, namely time of emergence of shoots (DAP), number of shoots (strands), length of cuttings (cm), root volume (cm3), fresh weight of shoots (grams) and dry weight of shoots (grams).